2021
DOI: 10.3390/ijerph18179422
|View full text |Cite
|
Sign up to set email alerts
|

Regional Travel as an Alternative Form of Tourism during the COVID-19 Pandemic: Impacts of a Low-Risk Perception and Perceived Benefits

Abstract: Previous COVID-19 tourism research has not considered the positive impact of a low-risk perception and a perception of the benefits of regional travel on taking alternative tourism. This study attempts to fill the research gap and examine the positive effect of these perceptions on tourists’ attitudes to regional travel and intentions to undertake regional travel during the COVID-19 pandemic. A survey of 278 respondents confirmed that the perceived benefit positively influences tourists’ attitudes and travel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The change in travel patterns (e.g. decline in long-distance flights, personal means of transport) and the reopening of tourism after the pandemic is an opportunity for sustainable tourism (Lama & Rai., 2021;Purcell et al, 2021), regional, rural or health tourism (Wang et al, 2021), which can be successfully implemented in Polish national parks.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The change in travel patterns (e.g. decline in long-distance flights, personal means of transport) and the reopening of tourism after the pandemic is an opportunity for sustainable tourism (Lama & Rai., 2021;Purcell et al, 2021), regional, rural or health tourism (Wang et al, 2021), which can be successfully implemented in Polish national parks.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The increase in the number of tourists in the BNP and nearby locations, despite high declines throughout the country, probably results from the change in travel patterns (tourists chose isolated 'safe' places, the number of long-distance trips decreased, etc.) as well as the development of regional, rural, health (Wang et al 2021) or sustainable tourism (Lama, Rai 2021;Purcell et al 2021). The BNP area is especially predestined to suit these forms of tourism.…”
Section: Discussionmentioning
confidence: 99%
“… Qiao et al (2021) investigated the role of positive mass media coverage in decreasing tourists’ self-protection motivations. Wang et al (2021) found that during the COVID-19 pandemic, a low-risk perception has a positive influence on tourists’ attitude toward undertaking regional travel. The above studies have indicated that, as an “infodemic” ( Williams et al, 2020 ), reliable and positive information on the COVID-19 pandemic may play a role in enhancing people’s travel intentions.…”
Section: Literature Reviewmentioning
confidence: 97%